Reseñas de libros de análisis cultural 18 (2021) - Rafael Manuel Mérida Jiménez; Verónica Sierra Blas; Nicolás Buckley; Cristina Suárez Toledano; Miguel Adrián Ramos García; Teresa Aguilar Solves; Claudio Rojas; Silvia Tévar Garcilópez (Kamchatka: Revista de Análisis Cultural)
Reseñas de los siguientes libros.